Expression of global consensus non-structural protein 1 (NS1) of dengue virus serotypes 1 and 2 in Nicotiana benthamiana - Le Nguyen, Cu; Ngoc Luong, Nguyen; Quoc Trieu, Tuong; Hoang Loc, Nguyen (Vietnam Journal of Biotechnology, 2023)
Dengue viruses, which consist of four distinct serotypes, belong to the Flavivirus family, one of the most important arthropod-borne pathogen groups for humans. Vietnam is among the tropical countries that have endemic dengue outbreaks, and in 2022, the number of infections as well as fatal cases reached a record high, causing a great economic burden to the public health system. Although all four dengue serotypes have been circulating in Vietnam, serotypes 1 and 2 have been dominating in the last few decades. Since most dengue clinical complications result from secondary infection with a different serotype from the first infection, prior knowledge of the proportion of a population having seropositive to a certain serotype is very crucial for public health policy makers. The absence of comprehensive and regular serological epidemiological surveys in Vietnam has impeded progress in surveillance and the implementation of effective preventive measures. To facilitate research into dengue treatment and diagnosis, we created two synthetic, codon-optimized genes encoding for global consensus non-structural protein 1 (NS1) from dengue serotypes 1 and 2. We expressed these genes in Nicotiana benthamiana using the agroinfiltration technique. Western blot using Dengue patients’ sera indicated that the target proteins were expressed, likely in both mono and multimeric forms. Our results indicated that N. benthamiana is a good alternative to other methods of producing recombinant NS1.